2021
DOI: 10.1007/s00371-021-02214-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of charisma, comfort and realism in CG characters from a gender perspective

Abstract: Realistic characters from movies, games and simulations can make viewers feel strange (discomfort), an effect known as the Uncanny Valley (UV) theory. However, can the genders of CG characters and the genders of viewers change perceived comfort? In addition, can the genders (both characters and viewers) also influence the perceived charisma? Can the realism of a character also influence these aspects? This work aims to evaluate the perception of women and men about female and male characters, created using Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Regarding H0 3 , firstly, as predicted in the work by Araujo et al [17], [18], our character, female and unrealistic, had values above 3 on the 5-Likert Scales (above average), that is, the character was considered charismatic and did not generate discomfort for the evaluated subjects. Regarding perceived comfort and charisma, we found some aspects that can be discussed: i) in most significant results about videos that started with positive macro expressions, people felt more comfortable and perceived more charisma in the character; ii) in most cases, people felt more comfortable and perceived more charisma in the characters in videos that had positive macro expressions followed by negative micro expressions than videos that had negative macro expressions followed by positive micro expressions; iii) looking at the averages in Table VIII, people felt more comfortable and perceived more charisma in the character in videos that started with macro positive expressions, especially in videos that had macro and micro positive expressions.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Regarding H0 3 , firstly, as predicted in the work by Araujo et al [17], [18], our character, female and unrealistic, had values above 3 on the 5-Likert Scales (above average), that is, the character was considered charismatic and did not generate discomfort for the evaluated subjects. Regarding perceived comfort and charisma, we found some aspects that can be discussed: i) in most significant results about videos that started with positive macro expressions, people felt more comfortable and perceived more charisma in the character; ii) in most cases, people felt more comfortable and perceived more charisma in the characters in videos that had positive macro expressions followed by negative micro expressions than videos that had negative macro expressions followed by positive micro expressions; iii) looking at the averages in Table VIII, people felt more comfortable and perceived more charisma in the character in videos that started with macro positive expressions, especially in videos that had macro and micro positive expressions.…”
Section: Discussionsupporting
confidence: 63%
“…The 3d character chosen in this work is available at https://www.turbosquid.com/FullPreview/Index.cfm/ID/917863. As shown in the work by Araujo et al [17], [18], cartoon and female (the character used in the work of Queiroz et al [2] was also female) characters tend to be more comfortable and charismatic to people. Therefore, we chose a female cartoon character to evaluate this hypothesis in relation to our character, independently if the micro or macro expressions are correctly identified.…”
Section: A Performed Experimentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically concerning CG characters, Araujo et al [23] recently presented a discussion about following questions: i) How does the comfort perceived by people of both tested genders (female and male) relate to the genders of the characters? and ii) Is the charisma influenced by the realism of the characters, considering the subjects and genders of the characters?…”
Section: Related Workmentioning
confidence: 99%
“…Charismatic characters can make people adore them. In the works by Araujo et al [4], [6], the authors found relationships between perceived charisma and perceived comfort about CG characters.…”
Section: Introductionmentioning
confidence: 97%